El Excentrico, 1966-04-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
April 5, 1966 [5 de abril de 1966]. Ano 16, No 12. Cover has picture of Barbara Larios with two other queen contestants. The headline reads, "Barbara Larios Queen Santa Clara G.I. Fourm 1966."